Advancing Critical Chemical Processes for a Sustainable Future: Challenges for Industry and the Max Planck–Cardiff Centre on the Fundamentals of Heterogeneous Catalysis (FUNCAT). (9th November 2022) - Bowker, Michael; DeBeer, Serena; Dummer, Nicholas F.; Hutchings, Graham J.; Scheffler, Matthias; Schüth, Ferdi; Taylor, Stuart H.; Tüysüz, Harun
Abstract: Catalysis is involved in around 85 % of manufacturing industry and contributes an estimated 25 % to the global domestic product, with the majority of the processes relying on heterogeneous catalysis. Despite the importance in different global segments, the fundamental understanding of heterogeneously catalysed processes lags substantially behind that achieved in other fields. The newly established Max Planck–Cardiff Centre on the Fundamentals of Heterogeneous Catalysis (FUNCAT) targets innovative concepts that could contribute to the scientific developments needed in the research field to achieve net zero greenhouse gas emissions in the chemical industries. This Viewpoint Article presents some of our research activities and visions on the current and future challenges of heterogeneous catalysis regarding green industry and the circular economy by focusing explicitly on critical processes. Namely, hydrogen production, ammonia synthesis, and carbon dioxide reduction, along with new aspects of acetylene chemistry. Abstract : This Viewpoint Article presents some of the research activities and visions of the newly established Max Planck–Cardiff Centre on the Fundamentals of Heterogeneous Catalysis (FUNCAT). Heterogeneous catalysis faces a number of challenges before a sustainable future may be achieved. Key concerns of FUNCAT are industrially relevant processes, such as green hydrogen production, ammonia synthesis, hydrogenation of carbon dioxide, and acetylene chemistry.